2018
DOI: 10.1002/hep.29707
|View full text |Cite
|
Sign up to set email alerts
|

The short‐term incidence of hepatocellular carcinoma is not increased after hepatitis C treatment with direct‐acting antivirals: An ERCHIVES study

Abstract: DAA treatment is not associated with a higher risk of HCC in persons with cirrhosis with chronic HCV infection in the short term. Previously reported higher rates of HCC associated with DAA treatment may be explained by both the presence of relatively fewer baseline HCC risk factors in persons treated with IFN as well as selection bias, given that DAA regimens were used to treat persons at higher risk for developing HCC. (Hepatology 2018;67:2244-2253).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
147
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 27 publications
(61 reference statements)
10
147
2
2
Order By: Relevance
“…Interestingly, unlike our results, a recent report indicated that DAA treatment was associated with an unexpected high rate of HCC . Investigators suggest that the high rate of HCC may actually be the results of the “warehousing effect”—a state where curative treatment was offered to those who were the sickest and were unable to be cured with the prior IFN treatment . A recent study of U.S. veterans found that DAA treatment was not associated with a higher risk of HCC in patients with HCV with cirrhosis .…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, unlike our results, a recent report indicated that DAA treatment was associated with an unexpected high rate of HCC . Investigators suggest that the high rate of HCC may actually be the results of the “warehousing effect”—a state where curative treatment was offered to those who were the sickest and were unable to be cured with the prior IFN treatment . A recent study of U.S. veterans found that DAA treatment was not associated with a higher risk of HCC in patients with HCV with cirrhosis .…”
Section: Discussioncontrasting
confidence: 99%
“…In a propensity score‐matched study, the incidence and recurrence of HCC was not different between patients treated with interferon and interferon‐free therapies . In a larger retrospective study using the electronically retrieved cohort of HCV infected veterans (ERCHIVES) database, the HCC incidence was similar among patients with cirrhosis who had achieved SVR after either interferon or DAA therapy . In our study, 70 of the 79 patients with advanced fibrosis did not have a diagnosis of HCC prior to therapy; of these 70 patients, 3 patients (4.3%) developed new HCC over a median follow‐up of 22 months.…”
Section: Discussionmentioning
confidence: 54%
“…(38) In a larger retrospective study using the electronically retrieved cohort of HCV infected veterans (ERCHIVES) database, the HCC incidence was similar among patients with cirrhosis who had achieved SVR after either interferon or DAA therapy. (39) In our study, 70 of the 79 patients with advanced fibrosis did not have a diagnosis of HCC prior to therapy; of these 70 patients, 3 patients (4.3%) developed new HCC over a median follow-up of 22 months. This rate is similar to the 3.16% reported after 24 weeks post-SVR among patients with cirrhosis in Italy, (40) 4.1% after a median follow-up of 15 months post-SVR among patients with cirrhosis in Austria, (41) and 4.5% after a median follow-up of 23 months post-HCV treatment in patients with all levels of fibrosis in Japan.…”
Section: Discussionmentioning
confidence: 55%
“…The panel A of Figure reproduces HCC incidence rates by treatment group according to SVR status in patients with cirrhosis, extracted from the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database . Strikingly, the HCC incidence rates observed in the SVR and non‐SVR subgroups were both consistently higher in the interferon‐free than in the interferon‐based treatment groups (although the differences reported in the paper were not significant due to a lack of power, our issue here concerns the order between incidence rates by treatment groups in the different SVR subgroups).…”
mentioning
confidence: 94%